IMPROVING FINANCIAL PERFORMANCE OF ISLAMIC BANK IN INDONESIA THROUGH ISLAMIC CORPORATE GOVERNANCE AND EARNING MANAGEMENT - Munifatussaidah, Asma; Nurrahmaningsih, Fauziah (UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
Abstrak: Penelitian ini bertujuan menganalisis pengaruh Islamic Corporate Governance dan Manajemen Laba terhadap Kinerja Keuangan Bank Syariah. Metode penelitian menggunakan pendekatan kuantitatif dengan data sekunder. Data penelitian diperoleh dari dua belas Bank Umum Syariah di Indonesia tahun 2018-2022, yang dipilih menggunakan teknik purposive sampling. Kemudian, teknik analisis yang digunakan adalah regresi data panel. Hasil penelitian ini menunjukkan bahwa Islamic corporate governance dan manajemen laba berpengaruh signifikan terhadap Kinerja keuangan bank syariah. Temuan penelitian ini memberikan bukti bahwa variabel Islamic corporate governance dapat membantu bank syariah di Indonesia dalam meningkatkan kinerja keuangan dengan adanya manajemen laba yang terkendali dari pihak bank syariah. Selain itu, temuan ini akan berkontribusi terhadap literatur mengenai variabel penentu kinerja keuangan bank syariah. Kata Kunci: Kinerja Keuangan, Islamic Corporate Governance, Manajemen Laba, Bank Syariah Abstract: This study aims to analyze the effect of Islamic Corporate Governance and Earning Management variable toward the Financial Performance of Islamic Banks. The examination technique utilizes a quantitative methodology with optional information. The exploration information were acquired from 12 (twelve) Islamic Business Banks in Indonesia in 2018-2022 period, which were selected using a purposive sampling technique. Then, the analysis technique uses Pooled Least Square of regression analysis technique. The results of this study indicate that Islamic corporate governance and earnings management have a significant effect on the financial performance of Islamic banks. The findings of this study provide evidence that Islamic corporate governance variables can assist Islamic banks in Indonesia, improving financial performance with controlled earnings management on the part of Islamic banks. Furthermore, these discoveries will add to the writing with respect to the determinants of Islamic bank monetary execution. Keywords: Financial Performance, Islamic Coporate Governance, Earning Management, Islamc bank.